Changes in Plamsa Concentrations of Hypoxanthine and Xanthine in Renal Vein as an Index of Delayed Kidney Allograft Function - Shahbazian, Heshmatollah; Mombini, Hayat; Zand Moghaddam, Ahmad; Jasemi, Majid; Hosseini, Mohammad Ali; Vaziri, Payam (Urology Journal, 2009)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; text-align:right; mso-pagination:widow-orphan; direction:rtl; unicode-bidi:embed; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman";} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt;} @page Section1 {size:612.0pt 792.0pt; margin:72.0pt 72.0pt 72.0pt 72.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> Introduction: The aim of this study was to evaluate the plasma levels of hypoxanthine (HX) and xanthine in the renal vein blood samples for prediction of delayed graft function (DGF). Materials and Methods: Two blood samples were taken from 47 kidney recipients, intraoperatively. The first sample was obtained from a peripheral vein before vascular anastomosis and the second from the allograft renal vein, 15 minutes after the anastomosis. Purine metabolites including xanthine and HX were measured and their associations with operative time, anastomosis time, frequency of clamping, urine output, and DGF were evaluated. Results: The mean levels of xanthine and HX were 0.12 ± 0.10 mg/L and 0.37 ± 0.17 mg/L in the first plasma samples, respectively. Thirty patients (63%) had no significant changes in neither of their purine metabolite levels and 17 (37%) had higher levels of HX, but not xanthine, in their second samples. Only anastomosis time had a significant relation with the level of the metabolites (P = .04). Three patients (10%) with no changes in the metabolites and 5 (29.4%) with higher HX levels had DGF (P = .12). The anastomosis time and frequency of vascular clamping were higher and the urine output after the anastomosis was lower in the patients with DGF. Conclusion: Cold ischemia in kidney transplantation causes a mild increase in the HX concentration indicative of short-term ischemia effects on the cell metabolism. But it cannot predict DGF. Anastomosis time, frequency of clamping, and urine output after the anastomosis are more sensitive indices.